2013
DOI: 10.1007/s12035-013-8591-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Huntington’s Disease Protein Impact on the ATM-Dependent Signaling and Repair Pathways of the Radiation-Induced DNA Double-Strand Breaks: Corrective Effect of Statins and Bisphosphonates

Abstract: Huntington's disease (HD) is a neurodegenerative syndrome caused by mutations of the IT15 gene encoding for the huntingtin protein. Some research groups have previously shown that HD is associated with cellular radiosensitivity in quiescent cells. However, there is still no mechanistic model explaining such specific clinical feature. Here, we examined the ATM-dependent signaling and repair pathways of the DNA double-strand breaks (DSB), the key damage induced by ionizing radiation, in human HD skin fibroblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
100
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 37 publications
13
100
1
Order By: Relevance
“…These findings, therefore, suggest that pATM is selectively sequestered by poly-GA deposits and that sequestration impairs DSB repair in C9orf72 cases. Interestingly, it was reported that mutant huntingtin also sequesters pATM in the cytoplasm and impairs the recruitment of pATM to sites of irradiation-induced DSB [16]. Therefore, we speculate that pATM sequestration might be a common feature in repeat expansion disorders.…”
Section: Discussionmentioning
confidence: 82%
“…These findings, therefore, suggest that pATM is selectively sequestered by poly-GA deposits and that sequestration impairs DSB repair in C9orf72 cases. Interestingly, it was reported that mutant huntingtin also sequesters pATM in the cytoplasm and impairs the recruitment of pATM to sites of irradiation-induced DSB [16]. Therefore, we speculate that pATM sequestration might be a common feature in repeat expansion disorders.…”
Section: Discussionmentioning
confidence: 82%
“…Accumulation of DNA damage is a normal effect of aging as are breakdown of proteostasis and disruption of the nuclear lamina [53, 54]. Protein aggregation indeed leads to breakdown of proteostasis [6, 7], as well as reduced response to DNA damage [55] and to disruption of the nuclear lamina [49]. All these effects accelerate aging by pushing the cells faster over the cliff.…”
Section: Discussionmentioning
confidence: 99%
“…In HD, cells transfected with mHTT fragments showed elevated DNA damage and ATM activation (23)(24)(25), and increased gH2AX was also found in fibroblasts from HD patients (24) and in HD mouse and patient striatal neurons (26). Intriguingly, HD patient cells exhibit radiosensitivity, albeit less than A-T cells, suggesting subtle dysfunction in the DNA damage response (27). Genetic reduction of p53, a molecule downstream of ATM mediating neuronal apoptosis, shows consistent benefits in cell, fly, and mouse models of HD (28).…”
Section: Introductionmentioning
confidence: 99%